2007
DOI: 10.1017/s0022215107001016
|View full text |Cite
|
Sign up to set email alerts
|

Quilting sutures for nasal septum

Abstract: Suturing of the nasal septum after septal surgery is a commonly performed procedure designed to prevent complications such as septal haematoma and bleeding. It is also useful for closing any inadvertent tears of the septal mucosa and providing additional support for the cartilage pieces retained in septoplasty. In addition, the suture can be placed through the middle turbinates, stabilising them during the healing process. Placing knots for interrupted sutures in the posterior and middle part of the nasal sept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 2 publications
(1 reference statement)
1
26
0
Order By: Relevance
“…Gottschalk, in 1978, described a modified suture technique, and found only 2 minor postoperative complications in cohort of 204 patients with septoplasty. Others have described modified techniques of the transseptal suture . Lemmens and Lemkens, Bajaj et al, and Ardehali and Bastaninejad all found the transseptal suture to be as effective as nasal packing in preventing postoperative complications such as hematoma and perforation.…”
Section: Discussionmentioning
confidence: 99%
“…Gottschalk, in 1978, described a modified suture technique, and found only 2 minor postoperative complications in cohort of 204 patients with septoplasty. Others have described modified techniques of the transseptal suture . Lemmens and Lemkens, Bajaj et al, and Ardehali and Bastaninejad all found the transseptal suture to be as effective as nasal packing in preventing postoperative complications such as hematoma and perforation.…”
Section: Discussionmentioning
confidence: 99%
“…Transseptal suture technique is described as a valid and comfortable alternative for packing. Quilting sutures are commonly described as continuous sutures in the literature [4,5,7]. However, we applied two to four horizontal, vertical or oblique separate sutures, changing according to the elevated parts of the septum.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, transseptal sutures have gained a broader application area, not only for preventing the complications such as septal hematoma and bleeding but also closing any accidental tears of the septal mucosa and providing additional support for the cartilage pieces retained in septoplasty. In addition, the sutures can be placed through the middle turbinates, stabilizing them during the healing process after endonasal surgeries [5]. Despite the fact that transseptal suturing has repeatedly been compared with nasal packing from diVerent aspects, we additionally evaluated their eVects on patients from an anaesthesiological perspective in this study.…”
Section: Introductionmentioning
confidence: 99%
“…This submucosal suture‐burying technique was also useful when a septal batten graft was placed. For membrane approximation methods such as quilting sutures, absorbable materials such as plain catgut or polyglactin are generally used, and thus no submucosal suture‐burying technique is needed . To obtain prolonged stability of the rejoined cartilages or fixated grafts, by contrast, we used polydioxanone sutures, which are absorbed more slowly than polyglactin sutures.…”
Section: Discussionmentioning
confidence: 99%